Identification of bilirubin reduction products formed by Clostridium perfringens isolated from human neonatal fecal flora - Vítek, Libor; Majer, Filip; Muchová, Lucie; Zelenka, Jaroslav; Jirásková, Alena; Branný, Pavel; Malina, Jirí; Ubik, Karel (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2006)
Urobilinoids belong to the heterogenous group of degradation products of bilirubin formed in the gastrointestinal tract by intestinal microflora. Among them urobilinogen and stercobilinogen with their respective oxidation products, urobilin and stercobilin, are the most important compounds. The aim of present study was to analyze the products of bacterial reduction of bilirubin in more detail. The strain of Clostridium perfringens isolated from neonatal stools, capable of reducing bilirubin, was used in the study. Bacteria were incubated under anaerobic conditions with various native as well as synthetic bile pigments, including radiolabeled unconjugated bilirubin (UCB). Their reduction products were extracted from media and separated following thin layer chromatography. Pigments isolated were analyzed by spectrophotometry, spectrofluorometry and mass spectrometry. In a special set of experiments, bilirubin diglucuronide was incubated with either bacterial lysate or partially purified bilirubin reductase and beta-glucuronidase to reveal whether bilirubin glucuronides may be directly reduced onto conjugated urobilinoids. A broad substrate activity was detected in the investigated strain of C. perfringens and a series of bilirubin reduction products was identified. These products were separated in the form of their respective chromogens and further oxidized. Based on their physical-chemical properties, as well as mass spectra, end-catabolic bilirubin products were identified to belong to urobilinogen species. The reduction process, catalyzed enzymatically by the studied bacterial strain, does not proceed to stercobilinogen. Bilirubin diglucuronide is not reduced onto urobilinoid conjugates, glucuronide hydrolysis must precede double bond reduction and thus UCB is reduced much faster.
Keywords: Feces; bilirubin; oxidace-redukce; Bilirubin; feces; Humans; spektrofotometrie ultrafialová; Mass Spectrometry; Spectrophotometry, Ultraviolet; chromatografie na tenké vrstvě; Oxidation-Reduction; Clostridium perfringens; hmotnostní spektrometrie; Chromatography, Thin Layer; lidé